Project Stakeholder Management in the Clinical Research Environment: How to Do it Right - Pandi-Perumal, Seithikurippu R.; Akhter, Sohel; Zizi, Ferdinard; Jean-Louis, Girardin; Ramasubramanian, Chellamuthu; Edward Freeman, R.; Narasimhan, Meera (Frontiers in Psychiatry, 2015)
This review introduces a conceptual framework for understanding stakeholder management in the clinical and community-based research environment. In recent years, an evolution in practice has occurred in which many applicants for public and non-governmental funding of public health research in hospital settings. Community health research projects are inherently complex, have sought to involve patients and other stakeholders in the center of the research process. Substantial evidence has now been provided that stakeholder involvement is essential for management effectiveness in clinical research. Feedback from stakeholders has critical value for research managers inasmuch as it alerts them to the social, environmental and ethical implications of research activities. Additionally those who are directly affected by program development and clinical research, the patients, their families, and others, almost universally have a strong motivation to be involved in the planning and execution of new program changes. The current overview introduces a conceptual framework for stakeholder management in the clinical research environment and offers practical suggestions for fostering meaningful stakeholder engagement. The fifth edition of PMBOK® of the Project Management Institute (PMI), has served as basis for many of the suggested guidelines that are put forward in this article.